Correlations of tumour permeability parameters with apparent diffusion coefficient in nasopharyngeal carcinoma. (October 2022) - Mui, Alan W.L.; Lee, Anne W.M.; Ng, W.T.; Lee, Victor H.F.; Vardhanabhuti, Varut; Man, Shei S.Y.; Chua, Daniel T.T.; Guan, X.Y.
Highlights: Vascular permeability is associated with diffusability in nasopharyngeal tumour. Both influx and reflux rates have inverse linear correlations with ADC. Reflux rate has the strongest inverse linear correlation with ADC. Abstract: Background and Purpose: Functional imaging has an established role in therapeutic monitoring of cancer treatments. This study evaluated the correlations of tumour permeability parameters derived from dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and tumour cellularity derived from apparent diffusion coefficient (ADC) in nasopharyngeal carcinoma (NPC). Material and Methods: Twenty NPC patients were examined with DCE-MRI and RESOLVE diffusion-weighted MRI (DW-MRI). Tumour permeability parameters were quantitatively measured with Tofts compartment model. Volume transfer constant (K trans ), volume of extravascular extracellular space (EES) per unit volume of tissue (Ve ), and the flux rate constant between EES and plasma (Kep ) from DCE-MRI scan were measured. The time-intensity curve was plotted from the 60 dynamic phases of DCE-MRI. The initial area under the curve for the first 60 s of the contrast agent arrival (iAUC60) was also calculated. They were compared with the ADC value derived from DW-MRI with Pearson correlation analyses. Results: Among the DCE-MRI permeability parameters, Kep had higher linearity in inverse correlation with ADC value (r = −0.69, p = <0.05). K trans (r = −0.60, p=<0.05) and iAUC60 (r = −0.64, p = <0.05) also had significant inverse correlations with ADC. Ve showed a significant positive correlation with ADC (r = 0.63, p = <0.05). Conclusions: Nasopharyngeal tumour vascular permeability parameters derived from DCE-MRI scan were correlated linearly with tumour cellularity measured by free water diffusability with ADC. The clinical implementations of these linear correlations in the quantitative assessments of therapeutic response for NPC patients may be worth to further explore.